2004
DOI: 10.1159/000081634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Administration of FR122047 (a Selective Cyclooxygenase 1 Inhibitor) and FR188582 (a Selective Cyclooxygenase 2 Inhibitor) on Prostaglandin-E<sub>2</sub>-Induced Aqueous Flare Elevation in Pigmented Rabbits

Abstract: Purpose: Two isoforms of cyclooxygenase (COX-1 and COX-2) exist. To determine in vivo effects of the intravenous administration of FR122047 (a selective COX-1 inhibitor), FR188582 (a selective COX-2 inhibitor), diclofenac sodium or dexamethasone phosphate disodium on prostaglandin-E2 (PGE2)-induced aqueous flare elevation and mRNA levels for COX-1 and COX-2 in pigmented rabbits. Methods: To produce aqueous flare elevation in rabbits, PGE2, 25 µg/ml, was applied to the cornea wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In addition, the NSAID (tepoxalin) used in that study was administered one hour before paracentesis (GILMOUR & LEHENBAUER, 2006). HAYASAKA et al (2003) and ABE et al (2004) demonstrated that topical or intravenous administration of nonsteroidal antiinflammatory drugs are able to suppress the protein influx to aqueous humor, only when used one hour and a half before the blood-aqueous barrier breakdown.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the NSAID (tepoxalin) used in that study was administered one hour before paracentesis (GILMOUR & LEHENBAUER, 2006). HAYASAKA et al (2003) and ABE et al (2004) demonstrated that topical or intravenous administration of nonsteroidal antiinflammatory drugs are able to suppress the protein influx to aqueous humor, only when used one hour and a half before the blood-aqueous barrier breakdown.…”
Section: Discussionmentioning
confidence: 97%
“…Nonsteroidal anti-inflammatory drugs suppress the protein influx to aqueous humor, after one hour and a half, whereas corticosteroids may need six hours after administration to show action by inhibitory effects on expression of the messenger RNAencoding cyclooxygenases-related protein (HAYASAKA et al, 2003;ABE et al, 2004). The reduction of only 27% in protein levels, contrasts the observations of a previous study, which proved that topical flurbiprofen, diclofenac, and suprofen were effective at preventing blood-aqueous barrier disruption after paracentesis in dogs (WARD, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…16 Potential unselective intrinsic effects of SC-560 on other components in the signaling cascade thus remain speculative. However, SC-560 is a frequently used inhibitor in rodent reperfusion-injury studies, and other selective COX-1 inhibitors like FR122047 33 and mofezolac 34 have not been tested. One might further speculate that selective COX-1 inhibition leads to a shift of the thromboxane/prostaglandin balance toward the prostaglandins, which in turn causes vasodilatation of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%